Caspase-1 knockout disrupts pyroptosis and protects photoreceptor cells from photochemical damage - Xiaoping Yu; Jiayuan Peng; Qian Zhong; Ailin Wu; Xiaoming Deng; Yanfeng Zhu (Molecular and Cellular Probes)
Aim: Retinal photochemical damage (RPD) plays a significant role in the development of various ocular diseases, with Caspase-1 being a key contributor. This study investigates the protective effects of Caspase-1 gene-mediated pyroptosis against RPD. Methods: Differentially expressed genes (DEGs) associated with RPD were identified through the analysis of two expression profiles from the GEO database. Correlation analysis was used to pinpoint pyroptosis-related genes (PRGs) linked to RPD. A Caspase-1 knockout 661 W cell line was generated via CRISPR-Cas9 gene editing, and single-cell colonies were screened and purified. Validation of knockout cells was performed through RT-qPCR, gene sequencing, and Western blot analysis. Comparative assays on cell proliferation, intracellular reactive oxygen species (ROS), and cytotoxicity were conducted between wild-type and Caspase-1 knockout cells under light exposure. Further RT-qPCR and Western blot experiments examined changes in the mRNA and protein levels of key pyroptosis pathway components. Results: Significant alterations in Caspase-1 expression were observed among PRGs. Homozygous Caspase-1 knockout cell lines were confirmed through RT-qPCR, genomic PCR product sequencing, and Western blot analysis. Compared to wild-type 661 W cells, Caspase-1 knockout cells exhibited higher viability and proliferation rates after 24 h of light exposure, alongside reduced LDH release. The expression of downstream pyroptosis factors at both the mRNA and protein levels was markedly decreased in the knockout group. Conclusion: CRISPR/Cas9-mediated Caspase-1 knockout enhanced the resistance of 661 W cells to photochemical damage, suggesting that Caspase-1 may serve as a potential therapeutic target for RPD-related diseases.